DAMPAK KREDIT PEGADAIAN TERHADAP PENINGKATAN PERKEMBANGAN USAHA PEDAGANG KECIL DIKABUPATEN KETAPANG - B01107081, Rachmat Hary Akbar (Jurnal Pembangunan dan Pemerataan, 2012)
ABSTRACT This study entitled "The Impact of Credit Pawnshop Business Development Toward Improved Small Traders In Ketapang". The problem in this research is how the "Impact Ketapang Pawnshop loans to increase business development for small traders Ketapang", while the purpose of this study to determine the impact of the credit given to the improvement of business development for small traders in the district Ketapang. This research used descriptive method, a method that describes the circumstances that actually occurred. Retrieval of data by using the kueosioner, interviews and observations. Sampling technique with a simple random sample of the total respondents 10% or 46 respondents as a small trader by profession pawnshop customers. The results of the study most of the respondents felt the real impact of the loans granted by the pawnshop, the visible impact of increased income business, assets increased efforts to make their business volume has increased so that the operating profit increased. Key word: Credit, Pawnshop Business, Small Traders